(3NQjOI GdbUQ hLQjOI GdYUQs - (3eMeO Hf eMeO Uaj GdOjf GHf fajS GdOjf MGeO Hf Cdg, CHh YHO Gddg, pYneGO GdpqOjf GdcGJH GdCUHgGfj , (B597 (3g` s; (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s
(3ChdgG (B:s
(3jHJOF bHjd GdcdGe Ydi CHj GdMSf GdYScQi GdeUQi s
(3BNQgG (B:s
(3jHJgi Edi GHf bGjO GdYSbdGfi s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B315 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B124 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B702s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs